Artigiani digitali. Per un modello innovativo di work related learning e di alternanza scuola-lavoro - Rinaldi, Walter (Studi sulla Formazione/Open Journal of Education, 2019)
We tackle the work related learning issue and the matter of the school job alternance in terms of innovative working experiences focusing on those not bound to conventional formative proposals. More specifically we refer to the role that creative careers can play in the remaking and rethinking of the city and we examine the possibilities of a creative training that pursues a tradition that combines arts and crafts, analyzing, at last, the role of the contemporary digital maker.